Life cycle assessment (LCA) of production and fractionation of bio-oil derived from palm kernel shell: A gate-to-gate case study - Chan, Yi Herng (Animo Repository, 2018)
This paper presents the life cycle assessment (LCA) of a novel process involving hydrothermal liquefaction of palm kernel shell (PKS) to produce bio-oil and subsequent extraction using supercritical CO2 (sc-CO2) to obtain a phenol-rich extract. In this study, five environmental impact categories, namely global warming potential (GWP), acidification potential (AP), eutrophication potential (EP), human toxicity potential (HTP), and photochemical ozone creation potential (POCP), were considered. In addition, a qualitative analysis on technology readiness level (TRL) on the interpretation of the LCA results was included. Lastly, conventional production of crude phenol was chosen as the benchmark for comparison to identify the environmental impact margins that need to be bridged in the future through process improvements. © 2018, Springer Nature Singapore Pte Ltd.